WIRELESS LAN NETWORK SECURITY METHOD WEP (Wired Equivalent Privacy) - Ogy Charles Sario Tamawiwy; Nenny Anggraini, Skom., MT. (Jurnal Sistem Komputer, 2008)
Scientific writing is about the WEP configuration on the WLAN network with RC4 encryption. The problem that arises is related aspects network security threats, strategic security and confidentiality of data in the network computer, the definition of encryption, definition kriptography algorithm, and algorithm functions.